P-118 METABOLIC DYSFUNCTION-ASSOCIATED STEATOTIC LIVER DISEASE: INDICATION FOR LIVER TRANSPLANTATION AND OCCURRENCE IN THE POSTOPERATIVE PERIOD - Felipe Ramos Caprini; Guilherme Massote Fontanini; Juarez Roberto de Oliveira Vasconcelos; Fernanda Fernandes Souza; Ajith Kumar Sankarankutty; Marcia Guimarães Villanova; Roberta Chaves Araújo (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: Metabolic dysfunction-associated steatotic liver disease (MASLD) is one of the most important causes of liver disease worldwide, and it is currently the main indication for liver transplantation.This study aims to evaluate (1) clinical-epidemiological profile of patients listed for liver transplant due to MASLD-related cirrhosis and mortality on the waiting list; (2) occurrence of allograft steatosis and new post-transplant comorbidities; (3) survival of patients with and without MASLD in the postoperative period. Patients / Materials and Methods: This retrospective study is based on a review of medical records of patients treated at the Liver Transplant outpatient clinic of the Hospital das Clínicas of the Faculty of Medicine of Ribeirão Preto - University of São Paulo, from 2005 to 2015. Results and Discussion: Of all patients listed for liver transplant (610), 10% had MASLD-related cirrhosis. Of these, 47.5% were female, with an average age of 56.3 years. These patients had higher MELD values (P = 0.01), higher rates of metabolic syndrome (P<0.05), and waiting list mortality of 42.6%. About transplant patients (264), 58 developed hepatic steatosis post-transplant, 82.8% of these with new steatosis and 17.2% with MASLD recurrence. The development of new comorbidities, such as diabetes and systemic arterial hypertension, was present in 26.2% and 22.5% of transplant recipients. Obesity and hypertension were the variables associated with a greater risk of allograft steatosis. The average survival of patients undergoing surgery was 8.7 years. Individuals transplanted for MASLD had significantly lower survival than those with other causes of cirrhosis (P=0.05). Conclusions: As MASLD is a highly prevalent disease, with different local realities, studies like this can serve as a basis for understanding the local reality and provide important information for developing public health programs.